Economic policy and state intervention selected papers of T N Srinivasan - Srinivasan, T N; Narayana, N S S (Ed.) (New Delhi Oxford University Press, 2001)
This book discuss long run issues dealt with in optimal growth model.The subsequent discussion on trade and foreign investment focuses on problems faced by developing countries.India`s economic problems,both internal and external,are examined in this cont
Keywords: Srinivasan, T N-Collections; India-Economic policy; Economic development